Discordance Between Patient and Clinician Experiences and Priorities in Rural Interhospital Transfer: A Mixed Methods Study. Issue 1 (14th July 2015) - Mohr, Nicholas M.; Wong, Terrence S.; Faine, Brett; Schlichting, Adam; Noack, Joseph; Ahmed, Azeemuddin
Abstract: Purpose: Rural emergency department (ED) patients require interhospital transfer for definitive care at nearly 6 times the national rate, yet transfer decision‐making is variable. The goal of this study was to understand patient experiences, preferences, and decision‐making in the rural interhospital transfer process, and to measure the concordance between patient opinions and provider perceptions. Methods: Ours is a mixed methods study of patients transferred to a 711‐bed Midwestern academic medical center and the emergency physicians in community hospitals. Qualitative interviews were conducted by a single research assistant with admitted patients transferred from an ED, and a corresponding survey was distributed to community emergency physicians. Standardized scenarios were posed to both groups to understand transfer priorities. Findings: Seventy‐nine patients and 40 physicians participated in this study. Patients and physicians cited proximity to home, medical expertise, a personal relationship with a health care provider, health insurance, privacy concerns, and patient choice as the primary factors that influenced patient transfer priorities. Compared with patient respondents, physicians overestimated the patient‐perceived importance of proximity to home ( P = .015) and being cared for by a personal physician ( P = .049), but they underestimated the value of receiving treatment in a comprehensive medical center ( P = .002). In standardized scenarios, physicians agreed with patients in transfer preferences for conditions requiring neurosurgical consultation, but they underestimated patients' desire for transfer for pneumonia requiring mechanical ventilation. Conclusion: Patients and physicians recognize similar factors that influence patient preferences in interhospital ED transfer, but physicians may overestimate the value of nonmedical influences on decision‐making priorities.